Ecological optima and tolerances of coastal benthic diatoms in the freshwater-mixohaline zone of the Río de la Plata estuary - Licursi, Magdalena (2010)
The purpose of this study was to explore the autecology of diatom species inhabiting the epipsammon and epiphyton in the freshwater-mixohaline zone of the Río de la Plata estuary. The diatoms are a conspicuous component of those communities. We discuss the optima and tolerance ranges of diatoms for the following environmental variables: conductivity, turbidity, pH, nutrients (phosphate, nitrate, nitrite, and ammonium), and dissolved oxygen levels as well as both the chemical and biological oxygen demand. The study was carried out on the Argentinean coastline between 34°27'S, 58°30'W and 35°23'S, 57°08'W. In total, 32 sampling sites influenced by different land uses were monitored along 168 km of shoreline. Epipsammic samples of the intertidal zone were taken at low tide during spring 2005, autumn and winter 2006, spring and summer 2007, and autumn 2008. Epiphytic samples were taken during summer, autumn, and spring 2000 and spring 2002. In total, 224 benthic species were identified in the 120 samples analyzed; 81 species had a frequency greater than 5% in the total sample dataset with more than 1% of relative abundance in at least 1 sample and were chosen for estimation of their optima and tolerances for selected water-quality characteristics. The physicochemical data analyzed indicated 2 gradients - increases in conductivity and turbidity along with decreases in the concentration of nutrients and organic matter - that generated different types of habitats for the species investigated.